A study of foot and ankle kinematics during stance phase of normal walking. (3rd December 2012) - Wang, Xue; Lu, Wen Feng; Loh, Han Tong; Wong, Yoke San; Ong, Fook Rhu
The study of foot and ankle kinematics is important in clinical cases such as abnormal foot functions and foot deformities. The objective of this study is to investigate kinematics of foot and ankle during stance phase of normal walking. This kinematic study includes joint motions between five rigid foot segments with new reference positions, and four new functional angles for describing physical features of walking. The results show that time–histories of the five joint motions present good agreement with previous literature. The new reference positions perform well for reducing variance among subjects. The results of four functional angles are consistent with gait and can more intuitively describe foot function features with good intra–subject repeatability. This study provides a comprehensive understanding of foot and ankle motions during stance phase of normal walking.